2021
DOI: 10.1088/2053-1583/ac1b6d
|View full text |Cite
|
Sign up to set email alerts
|

Narrow bands, electrostatic interactions and band topology in graphene stacks

Abstract: The occurrence of superconducting and insulating phases is well-established in twisted graphene bilayers, and they have also been reported in other arrangements of graphene layers. We investigate three such arrangements: untwisted AB bilayer graphene on an hBN substrate, two graphene bilayers twisted with respect to each other, and a single ABC stacked graphene trilayer on an hBN substrate. Narrow bands with different topology occur in all cases, producing a high density of states which enhances the role of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…This explains why significant band deformations are not observed in tDBLG even though the Hartree potential has a similar magnitude as the band width close to the magic angle. A similar explanation for the absence of strong band deformations was also offered in the continuum model of reference [70].…”
Section: Doping Dependent Band Structuresupporting
confidence: 63%
“…This explains why significant band deformations are not observed in tDBLG even though the Hartree potential has a similar magnitude as the band width close to the magic angle. A similar explanation for the absence of strong band deformations was also offered in the continuum model of reference [70].…”
Section: Doping Dependent Band Structuresupporting
confidence: 63%
“…We have focused on TBG here, but many more moiré materials comprised of graphene exist. [87,88] Perhaps the most promising ones are where there is a ±𝜃 twist between each adjacent graphene layer. [84,[89][90][91][92][93][94][95] These moiré graphene multilayers have been shown to host highly tunable superconducting phases, [96][97][98][99][100] and as the number of layers increases, the superconducting phase occurs over wider and wider doping ranges.…”
Section: Discussionmentioning
confidence: 99%
“…In twisted bilayer-bilayer graphene, Cao et al found a rich phase diagram with tunable correlated insulator states and spin-polarized phases [9]. Culmination of these recent experimental achievements has motivated theoretical studies on exotic correlated electronic phases in graphene superlattices [10][11][12][13][14][15][16][17].…”
Section: Introduction-mentioning
confidence: 99%